The cinema book - Cook, Pam 1943- (British Film Institute, 1985)
This volume is a guide to understand the movies. Prepared by the British Film Institute and published in Britain, the editor includes information on film history and theory, stars, and "authorship" offers discussion and analysis. Divided into five main sections --- History, Genre, Authorship, History of Narrative, and Narrative and Structuralism --- each is separately authored by writers who argue from their different perspectives on film theory and criticism.